Regulation of penicillin-binding protein activity: description of a methicillin-inducible penicillin-binding protein in Staphylococcus aureus. - Rossi, L (1985)
The penicillin-binding proteins (PBPs) of two methicillin-resistant strains of Staphylococcus aureus (R2 and R1) were analyzed in cells grown in the absence and in the presence of methicillin. Under the former condition, strain R2 showed the typical PBP pattern of beta-lactam-susceptible strains, while strain R1 showed a markedly increased amount of PBP-3. Under the latter condition, on the other hand, a novel PBP (PBP-2a) located between PBP-2 and -3 was detected in strain R2, while strain R1 appeared to synthesize an even greater amount of PBP-3, in respect to untreated cells. Both R2 PBP-2a and R1 PBP-3 showed a very low affinity for methicillin, which was consistent with the MICs for the respective strains.